Is Liquid Democracy Compatible with Representative Democracy? Insights from the Experience of the Pirate Party Germany - Deseriis, Marco (PARTECIPAZIONE E CONFLITTO, 2022)
Although political scientists and political theorists rarely recognize liquid democracy (LD) as a distinct model of democracy, LD has its own history, theoretical underpinnings and practical applications. The article fills this gap by conceptualizing LD as an original decision-making procedure and a mode of political representation based on mechanisms of authorization and accountability that are fundamentally different from parliamentary representation. Yet the first practical applications of LD have occurred within representative institutions such as the German Federal Parliament and political organizations such as the Pirate Party Germany. These have experimented with two different LD software, Adhocracy and Liquidfeedback, whose design enables two variants of LD, the former aimed at assessing the quality of opinions and the latter aimed at transforming experts into decision-makers. After examining the impact of the adoption of Liquidfeedback on the internal organization of the Pirate Party, the article identifies two challenges that have emerged through the use of LD software: the conflict between the participants' right to privacy and the transparency of delegated decisions; and the concentration of power in the hands of few delegates. The article concludes by noting that only the variant of LD oriented toward assessing the quality of opinions is fully compatible with representative democracy.